Body Composition and Basal Metabolic Rate in Women with Type 2 Diabetes Mellitus - Marina de Figueiredo Ferreira; Filipe Detrano; Gabriela Morgado de Oliveira Coelho; Maria Elisa Barros; Regina Serrão Lanzillotti; José Firmino Nogueira Neto; Emilson Souza Portella; Haydée Serrão Lanzillotti; Eliane de Abreu Soares (Journal of Nutrition and Metabolism)
Objective. The aim of this study was to determine which of the seven selected equations used to predict basal metabolic rate most accurately estimated the measured basal metabolic rate. Methods. Twenty-eight adult women with type 2 diabetes mellitus participated in this cross-sectional study. Anthropometric and biochemical variables were measured as well as body composition (by absorptiometry dual X-ray emission) and basal metabolic rate (by indirect calorimetry); basal metabolic rate was also estimated by prediction equations. Results. There was a significant difference between the measured and the estimated basal metabolic rate determined by the FAO/WHO/UNU (Pvalue<0.021) and Huang et al. (Pvalue≤0.005) equations. Conclusion. The calculations using Owen et al’s. equation were the closest to the measured basal metabolic rate.